2003
DOI: 10.1046/j.1447-0349.2003.t01-4-.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of a professional practice audit questionnaire for mental health nursing in Aotearoa/New Zealand

Abstract: This paper reports the three-stage development of a professional practice audit questionnaire for mental health nursing in Aotearoa/New Zealand. In Study 1, clinical indicator statements (n = 99) generated from focus group data, which were considered to be unobservable in the nursing documentation in consumer case notes, were included in a three-round Delphi process. Consensus of ratings occurred for the mental health nurse and academic participants (n = 7) on 83 clinical indicator statements. In Study 2, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The applicability and universality of the O'Brien et al . clinical indicators applied to the international mental health sector [1, 35–37], now need to be determined. Could the tools described here be modified for appropriateness to the Australian context and beyond?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The applicability and universality of the O'Brien et al . clinical indicators applied to the international mental health sector [1, 35–37], now need to be determined. Could the tools described here be modified for appropriateness to the Australian context and beyond?…”
Section: Discussionmentioning
confidence: 99%
“…The project used a four-stage research design that included (i) focus groups of expert Maˆori and non-Maˆori mental health nurses to generate statements of best mental health nursing practice; (ii) Delphi surveys to prioritize and validate the statements [33]; (iii) a pilot study and (iv) national audit of patient case notes to further validate and assess the interrater reliability of the clinical indicators [34]. A professional practice audit questionnaire made up from items unobservable in patient case notes was also trialled [35]. The project had ethical clearance from all participating District Health Board human ethics committees and Massey University human ethics committee.…”
Section: Summary Of the Research Designmentioning
confidence: 99%
“…As shown in Table 4, the mean rate of CNCI occurrence for each standard of practice ranged from 49% in standard one (culturally safe care) to 77% in standard three (nursing care that reflects contemporary practice and is consistent with the therapeutic plan). The national field study results of the questionnaire, that includes clinical indicator statements for all ANZCMHN (1995a) standards, are reported elsewhere (Hardy et al 2004; Gaskin et al 2003; Gaskin et al 2004; O’Brien et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…A Professional Practice Audit Questionnaire (O’Brien et al . 2002d) was also developed to assess the achievement of a second set of clinical indicator statements, for which achievement was not observable in consumer case note documentation (Gaskin et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While in other studies it has been found that nurses consider service user strengths and work within a recovery‐orientated framework (Cowman et al . 2001, Gaskin et al . 2003), only one respondent in this study mentioned the need to gather information about the service user's opinion as part of the content of a comprehensive mental health nursing assessment.…”
Section: Discussionmentioning
confidence: 99%